Effect of allopurinol on all-cause mortality in adults with incident gout: propensity score–matched landmark analysis - Kuo, Chang-Fu; Grainge, Matthew J.; Mallen, Christian; Zhang, Weiya; Doherty, Michael (Oxford University Press, 2015)
Objective: To examine the association between allopurinol use and all-cause mortality for patients with incident gout.